Analysing and Modelling Inaccessibility in Dependable Real-Time Networks - Souza, Jeferson L. R.; Siqueira, Frank (Anais do Latin-American Symposium on Dependable Computing (LADC), 2022)
Every disregarded aspect of the network operation becomes a real threat for safety-critical environments. As a measure to better assess the dependability and timeliness properties of networking communications, this paper advances the state-of-the-art on dependable real-time networking communications by providing a powerful yet simple formalisation, which supports the characterisation, analysis, and understanding of temporal deviations observed on communication networks, as consequence of network errors. As part of such formalisation, the Theorem of Inaccessibility is focused on the domain of time, where its application allows all the uncertainty related to the movement of energy through the space domain, which is associated with electromagnetic waves, to get confined and transparent. Our approach can help researchers, professionals, and practitioners to recognise the existence of network inaccessibility, in order to understand how it affects wired/wireless networks and critical services that rely on them for exchanging data on a dependable, timely, and therefore predictable way.